The Sandwich Shack / Ak Mohd Khairulikhwan… [et al.] - Khairulikhwan, Ak Mohd; Yahya, Mohd Hafizuddin; Laudin, Mohamad Faizal; William, Marcel (Faculty of Business Management, Universiti Teknologi MARA, 2014)
The Sandwich Shack is a company that aims to produce a steady supply of healthy fast foods and beverages to our health-conscious customers all around Sabah with the potential of expanding not just in Malaysia, but on a global scale. Our product menu varies from several types of healthy yet delicious sandwiches, salads, and freshly made juices which are sold at a reasonable price. Our customers would range from the toddlers, tweens, teens, adults and even the elderly. The company name originates from our mam product in the menu which are the sandwiches. We planned to start of our business in a kiosk in which resembles a shack that sells sandwiches. Therefore, the name "The Sandwich Shack" became our official company name. In our business partnership, the distribution of position consists of the General manager, marketing manager, Financial manager, Operation manager and last but not least the Administration manager. Our business operates seven days a week.